2006
DOI: 10.1093/ps/85.8.1490
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Chick Conformation and Quality Measures with Early Growth Traits in Males of Eight Selected Pure or Commercial Broiler Breeder Strains

Abstract: Current commercial broiler products are derived from the crosses of various strains at the primary breeder level. This study investigated chick development, yolk utilization, and early growth rate of males from 8 broiler breeder strains. These strains were a combination of both specialized and commercial-line products. At hatch, 110 male chicks per strain were weighed and wing-banded, and chick quality was assessed. Traits included navel condition, hock color, chick length, shank length, and abdomen score by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
7
31
2
1
Order By: Relevance
“…Similar results are concluded by Willemsen et al (2008). The relationship between chick weight and chick length was in the chronic high temperature group, and it was supported by the other findings of Wolanski et al (2006) and Willemsen et al (2008). A significant correlation between yolk-free chick weight and chick length was found only in the acute high temperature group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results are concluded by Willemsen et al (2008). The relationship between chick weight and chick length was in the chronic high temperature group, and it was supported by the other findings of Wolanski et al (2006) and Willemsen et al (2008). A significant correlation between yolk-free chick weight and chick length was found only in the acute high temperature group.…”
Section: Discussionsupporting
confidence: 86%
“…The third method is better than second one, because chick-hatching weight includes the actual chick weight and residual yolk sac weight. The last scoring method is the chick length that is measured from the tip of the beak to the middle toe (Deeming 2005;Wolanski et al 2006). Some researchers found a positive correlation between chick length and body weight at 42 days of age (Hill 2001;Meijerhof 2006;Molenaar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the correlation between chick weight and chick length; however, most of these have been conducted with broiler chickens. Wolanski et al (2006), found a correlation of 0.303 between chick weight and length of broiler chickens. In this study, a correlation of 0.355 was found between chick weight and length; however, this correlation was not significant (Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…A smaller yolk sac percentage would suggest greater transfer of nutrients, immune bodies, and metabolic information to the hatchling as well as greater appetite as discussed below. The absorption of nutrients from the yolk sac has been reported to be essential to promote subsequent growth (Murakami et al, 1992;Bigot et al, 2001) and early hatching chicks may have had an advantageous developmental and growth pattern (Lamot et al, 2014) due to earlier absorption of the yolk that has typically represented approximately 10% of total BW at initial hatching (Sklan et al, 2000;Wolanski et al, 2006). Early utilization of the yolk could have produced a metabolically more mature chick that was ready to consume feed and concurrently utilize the remaining residual yolk sac materials (Chamblee et al, 1992;Noy & Sklan, 1998b;Halevy et al, 2003;Tona et al, 2003;Yang et al, 2008;Careghi et al, 2005;Bhanja et al, 2009;Shinde et al, 2015).…”
Section: Yolk Sac Percentagementioning
confidence: 99%
“…Obviously, early hatching chicks have frequently exhibited a different developmental and growth pattern than did middle or late hatching chicks (Lamot et al, 2014;Brake et al, 2015), which may simply be related to differences in initial appetite. This may be related to having differences in residual yolk sac that may approximate 10% of total BW (Sklan et al, 2000;Wolanski et al, 2006). Residual yolk has been demonstrated to be important to the complex metabolic processes involved in early chick development (Noy & Sklan, 1998a;Noy et al, 2001;Halevy et al, 2003;Tona et al, 2003;Careghi et al, 2005) but required feed consumption to facilitate rapid absorption (Chamblee et al, 1992;Henderson et al, 2008), which has seemed to be greater in early hatching chicks.…”
Section: Introductionmentioning
confidence: 99%